Spin-fluctuation glue disfavors high-critical temperature of superconductivity? - Hiroyuki Yamase (New Journal of Physics, 2023)
Antiferromagnetic fluctuations are believed to be a promising glue to drive high-temperature superconductivity especially in cuprates. Here, we perform a close inspection of the superconducting mechanism from spin fluctuations in the Eliashberg framework by employing a typical one-band model on a square lattice. While spin fluctuations can eventually drive superconductivity as is well established, we find that the superconducting tendency is suppressed substantially by a seemingly negligible contribution from a small momentum transfer far away from $(π,π)$ . This suppression comes from phase frustration of the pairing gap and is expected to be a general feature due to the repulsive pairing interaction of spin fluctuations. Furthermore, we find that the momentum dependence of the pairing gap largely deviates from the functional form of $\cos k_{x} - \cos k_{y}$ , although this form is well established in cuprate superconductors. We argue that an instantaneous magnetic interaction plays the important role to understand high-critical temperature of superconductivity as well as the momentum dependence of the pairing gap.